1993
DOI: 10.1055/s-2006-959981
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some Pharmacodynamic Effects ofMentha longifoliaExtracts

Abstract: Huinulus lupulus L. (hop) (Cannabidaceae) has been reported to have hypnotic and sedative effects (1-3). But there have been few recent reports concerning the detailed behavioral effects of the hop. Thus, we have investigated the CNS effects of Humulus lupulus (hop) extract using several behavioral tests, such as spontaneous locomotor activity, rotarod test, potentiation of pentobarbital-induced sleep, hypothermic, analgesic, and anticonvulsant tests in mice. Hop extracts (Emil Flachsmann AG) was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies have shown that inhalations of various species of peppermint were effective in reducing muscle pain and fatigue as well as they had muscle relaxation effect [ 46 – 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that inhalations of various species of peppermint were effective in reducing muscle pain and fatigue as well as they had muscle relaxation effect [ 46 – 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that various kinds of mint were effective in reducing muscle pain [19,20], muscle relaxation, and reduce fatigue [21]. However, previous studies showed inhaling peppermint aroma has no effect on the lung function tests and physical performance during acute and intensive exercise [18].…”
Section: Discussionmentioning
confidence: 99%